Preparation and Characterization of Chitosan/Titanium Dioxide Film for Electrochemical Sensing Applications - Nasution, Astri Anjelina; Nainggolan, Irwana; Andriayani, Andriayani; Alva, Sagir (Talenta Publisher, 2026)
Chitosan/TiO₂-modified electrodes were characterized using the cyclic voltammetry method. The electrodes were fabricated through an electrodeposition technique to produce a coating on the substrate surface. TiO₂ concentrations of 50, 100, 150, 200, and 250 mg/L were used. The chemical structure and functional group interactions of the films were characterized using Fourier Transform Infrared (FTIR) spectroscopy, which revealed characteristic chitosan functional groups and Ti–O–Ti stretching bands, indicating the dispersion of TiO₂ within the chitosan matrix. The electrochemical performance of the electrodes was evaluated in phosphate-buffered saline (PBS) solution at pH 7. The results showed that the chitosan/TiO₂ concentration variation of 150 mg/L produced the highest anodic current response, while the optimum scan rate was obtained at 75 mV/s. A linear relationship between peak current and scan rate was obtained, with a regression equation of y = 0.0014x + 0.3788 and a coefficient of determination (R²) of 0.9869, indicating a strong linear correlation. Based on these results, the chitosan/TiO₂ material exhibited electrochemical responses with potential for further development in electrochemical sensing applications.